Pyrazine-based organometallic complex: synthesis, characterization, and supramolecular chemistry - Bhowmick, Sourav; Chakraborty, Sourav; Das, Atanu; Rajamohanan, P. R.; Das, Neeladri (Inorganic Chemistry, 2015)
The design, synthesis, and characterization of a new pyrazine-based ditopic platinum(II) organometallic complex are reported. The molecular structure of the organoplatinum pyrazine dipod was determined by single-crystal X-ray crystallography. The potential utility of this organometallic ditopic acceptor as a building block in the construction of neutral metallasupramolecular macrocycles containing the pyrazine motif was explored. Pyrazine motifs containing supramolecules were characterized by multinuclear NMR (including H-1 DOSY), mass spectrometry, and elemental analysis. The geometry of each supramolecular framework was optimized by employing the PM6 semi-empirical molecular orbital method to predict its shape and size. The ability of the pyrazine-based organoplatinum complex to act as a host for nitroaromatic guest (2,4-dinitrotoluene and PA) molecules was explored by isothermal titration calorimetry (ITC). The binding stoichiometry and thermodynamic parameters of these host guest complexation reactions were evaluated using ITC. Theoretical calculations were performed to obtain insight into the binding pattern between the organometallic host and nitroaromatic guests. The preferable binding propensity of the binding sites of complex 1 for both nitroaromatics (PA and 2,4-dinitrotoluene) determined by molecular simulation studies corroborates well with the experimental results as obtained by ITC experiments.